MEDIASI KONFIGURASI STRUKTURAL DALAM HUBUNGAN SERVANT LEADERSHIP STYLE PADA KINERJA - Umama, Hany Azza; Handika, Firdanis Setyaning (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
Research on leadership styles is still in great demand by researchers, considering that what leadership style is the best to apply. This study is a follow-up study from Eva (2001) which is recommended to analyze more deeply about the structural configuration of servant leadership style with performance because the relationship states that the formal structure acts as a substitute for servant leadership on job satisfaction. This is of course contrary to the results of previous studies which state that servant leadership has a positive effect on performance and satisfaction. In addition, according to the researcher, research on servant leadership style by linking the configuration of construction is still few researchers want to investigate further about mediating the configuration of construction in the relationship of servant leadership style with performance. Collecting data in this study using a primary can, namely a questionnaire, where the questionnaire will be given randomly using a g-form by distributing it through electronic media to employees of corporate educational institutions and others. In addition to using primary data from the questionnaire, secondary data will also be used by researchers to support the analysis of this research. The control variables in this study were age, gender and years of service using the Sobel test as an analytical tool to see the moderating effect. The results showed a significant relationship between servant leadership style on formalization, formalization on performance and servant leadership on performance. What is interesting in this study is that the magnitude of the relationship between servant leadership and performance through formalization is actually lower than the direct relationship. This shows that the feel of servant leadership style is able to produce formalization in relation to performance. This is possible if there is group maturity. Groups or employees who are considered mature are employees who understand their duties and obligations, so that no formalization actually provides high performance. Re-testing is very necessary considering that the assessment of the construct is still not carried out. this will add to the repertoire of knowledge about servant leadership, structure and performance.